Program Coordinator Professional Development Series - Amy Miller Juve; Cindy Koonz; Christine Flores; Sue Simmons (Association of American Medical Colleges, 2015)
Abstract Introduction Program coordinators (PCs) are vital to the success of residency and fellowship training programs. They are responsible in partnership with other program leadership for ensuring trainees receive the highest quality of education and ensuring programs meet institutional and national requirements. Although PCs play an important role in graduate medical education (GME), many report being ill prepared to perform their job duties. One way in which institutions can ensure PCs are being properly trained is to offer an institution-wide PC professional development (PCPD) course. In this resource, we describe and offer materials from a PCPD series at Oregon Health & Science University. The target audience is leaders in GME who have the ability and desire to implement a professional development series for PCs. Methods The series was designed to be offered over three years: bronze (foundational topics), silver (intermediate topics), and gold (advanced topics). The developers created the bronze level to be offered in the first year of the series, as an introduction to GME and to cover foundational knowledge that all coordinators should have in order to perform job functions. The silver level includes topics that are more advanced than bronze and intended to build upon knowledge previously gained in the bronze level. The gold level was developed for PCs who complete both the bronze and silver levels. It is intended to help PCs develop leadership skills and contribute in a substantial way to the quality of their training program. Results Based on participants' postsession survey data, 99% agreed or strongly agreed that they gained something useful from participating, and 96% agreed or strongly agreed to having an improved understanding of the content areas covered and felt that the information learned would help them do their job better. Postsession written comments included "it is very helpful to learn from other PC's," "topics covered in these sessions were very beneficial," and "it was a great learning experience and the quality & obvious forethought of these sessions really communicated something about the professionalism of this series and the value being placed on our time and learning." Discussions Several sessions have resulted in additional exploration of content areas outside of the PCPD series in the form of brown-bag discussions that have included PC participation from across training programs.